1989
DOI: 10.1161/01.res.65.5.1417
|View full text |Cite
|
Sign up to set email alerts
|

Significance of myocardial alpha- and beta-adrenoceptors in catecholamine-induced cardiac hypertrophy.

Abstract: The role of alpha- and beta-adrenoceptors in the development of catecholamine-induced cardiac hypertrophy in vivo was investigated. Rats received a constant intravenous infusion of norepinephrine or sodium chloride (control) for 3 days. The norepinephrine infusion was combined with the alpha-blocker prazosin, the beta-blocker metoprolol, or both blockers. For modulation of the work load of the heart, the calcium channel blocker verapamil was added to the norepinephrine infusion. A further group of animals was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
71
0
2

Year Published

1992
1992
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(77 citation statements)
references
References 31 publications
4
71
0
2
Order By: Relevance
“…2,20 The reninangiotensin system was proposed to be involved in the development and maintenance of Iso-induced CH. 5,6 More recently, activation of 44-to 42-kDa extracellular signalregulated protein kinases through a calcineurin-dependent mechanism was shown to participate in the development of Iso-induced CH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,20 The reninangiotensin system was proposed to be involved in the development and maintenance of Iso-induced CH. 5,6 More recently, activation of 44-to 42-kDa extracellular signalregulated protein kinases through a calcineurin-dependent mechanism was shown to participate in the development of Iso-induced CH.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between cardiac mass and sympathetic activity was found in young hypertensive humans, 1 and long-term infusion of subpressor doses of norepinephrine leads to CH in dogs and rats. 2,3 This cardiotrophic effect of catecholamines involves both ␣-or ␤-adrenergic receptors. 4 It is well recognized that repeated or continuous injections of the ␤-adrenoceptor agonist isoproterenol (Iso) causes, within days, clear CH, 5 and therefore it represents a useful experimental model.…”
mentioning
confidence: 99%
“…Recent data suggest that a specific cardiac fibroblast-derived factor in turn augments the Ang IIinduced myocyte growth [67]. Other trophic hormones for cardiomyocytes that are present in abundance, especially in decompensated cirrhosis, are endothelin and norepinephrine, and both can cause cardiac hypertrophy even in the absence of stretch [68,69].…”
Section: Diastolic Dysfunctionmentioning
confidence: 99%
“…1 AR agonists such as norepinephrine (NE) (␣ and ␤), phenylephrine (PHE) (␣), and isoproterenol (ISO) (␤) have been reported to induce cardiomyocyte hypertrophy (2)(3)(4)(5)(6)(7). Prolonged infusion of subpressor doses of NE increases the mass of the myocardium and the thickness of the left ventricular wall, suggesting that NE has direct hypertrophic effects on cardiac myocytes without affecting afterload (2).…”
mentioning
confidence: 99%
“…Both in vivo and in vitro studies demonstrate that ISO also stimulates expression of proto-oncogenes in cardiomyocytes and induces cardiac hypertrophy (6,9,10). Activation of each AR evokes specific intracellular signals (4,11). It has been shown that stimulation of ␣ 1 -AR activates phosphoinositide-specific phospholipase C via G q protein and hydrolyzes phosphoinositide 4,5-bisphosphate into inositol 1,4,5-triphosphate and diacylglycerol.…”
mentioning
confidence: 99%